Understanding spatio‐temporal rainfall‐runoff changes in a semi‐arid region. Issue 11 (27th March 2020) - Aryal, Santosh K.; Silberstein, Richard P.; Fu, Guobin; Hodgson, Geoff; Charles, Stephen P.; McFarlane, Don
Abstract: The rainfall‐runoff response in arid and semi‐arid regions is very different from that in humid or temperate regions due to factors including the relative difference in magnitude of rainfall and potential evaporation and the absence of sustained base flow. Despite being infrequent and of short duration, rainfall and runoff events sustain regional ecosystems through flooding and groundwater recharge. Understanding spatial and temporal hydrological patterns and their changes together with inter‐relations of hydrological variables can provide insight into the current and future water resource in these regions. However, scarcity of data, small numbers of flow events and access difficulties make study of arid zone hydrology difficult. This study carried out quantitative hydrological analysis using regional‐scale data from a semi‐arid region in northern Western Australia and compared the findings with those from other similar regions of the world. We found that the regional runoff showed a spatial pattern that does not correlate closely with the rainfall across the region. The mean peak annual floods per unit catchment area were similar to those from many other arid and semi‐arid regions of the world, despite cyclonic rainfall. Furthermore, the annual runoff showed high temporal and spatial variations with little to no carry‐over from the past at an annual time scale. We found statistically significant covariance between the hydrological variables such as mean annual runoff, number of flow days, high flows and drought‐like conditions. The mean annual runoff and runoff ratio however showed no significant correlation with catchment area. Despite increasing trends in annual and seasonal rainfall in recent years, the annual and seasonal flow trends were quite small and exhibited much lower rainfall elasticity of runoff than in other semi‐arid regions across the world. However, part of the region had a 44% increase in rainfall during a 7‐year period, which nearly doubled the runoff. Key findings: Annual and seasonal runoff trends can be considerably different from corresponding rainfall trends for a variety of reasons. Runoff spatial variability patterns may not follow the rainfall spatial variability. Mean annual runoff can be uncorrelated to catchment area or mean annual rainfall in semi‐arid regions. Despite prevalence of cyclonic rainfalls, mean annual peak flows in the Pilbara semi‐arid study region are similar to those in most other semi‐arid regions elsewhere. Abstract :